Investigating Color Idioms and their Translation from English into Arabic - Khalid Abdullah Al-Shaikhli / Jordan (College of Education for Women, 2019)
Colors are universal, and throughout the ages, they have been associated with various religious, social and spiritual meanings. They symbolize a galaxy of things to designate certain ideas or symbols that are sometimes contradictory. The present study is an attempt to investigate colors, their meanings and symbolism, and the approaches to translating color idioms from English into Arabic. It fathoms one of the thorny areas for translation theorists let alone practitioners. Various definitions, classifications of types and symbolism across cultures are provided. After reviewing idioms and methods of translating them, a survey of 114 sentences that include color idioms was conducted to see which method is mostly adopted by professionals. The survey has revealed that, among the methods available for the translator, the most common strategy in translating color idioms from English into Arabic is paraphrase, followed by loan translation. In addition, the equivalent effect principle sought by Nida (1964) would not be achieved and the color element found in the source language is lost in translation, simply because it has neither linguistic nor cultural correspondent equivalent in the target language.